Glyptothorax lanceatus, a new species of sisorid catfish (Teleostei: Siluriformes) from southwestern China - Ng, Heok Hee; Jiang, Wan-Sheng; Chen, Xiao-Yong (Zootaxa, 2012)
Glyptothorax lanceatus, a new species of sisorid catfish from the upper Salween River drainage in southwestern China,is described. It can be distinguished from congeners in having the following combination of characters: length of nasalbarbel 18.1–21.5% HL; length of maxillary barbel 86.2–91.1% HL; length of inner mandibular barbel 23.8–28.2% HL;length of outer mandibular barbel 42.8–49.1% HL; eye diameter 6.8–8.3% HL; interorbital distance 20.2–22.1% HL;elongate, ovoid tubercles on dorsal surface of head; head length 23.0–25.1% SL; head width 16.3–18.8% SL; width ofadhesive apparatus 1.60–1.74 times in its length; depressed area in thoracic adhesive apparatus not wholly enclosed byridges; ridges of thoracic adhesive apparatus not extending onto gular region;10–13 serrations on posterior edge of pecto-ral spine; pectoral-fin length 21.1–24.5% SL; length of adipose-fin base 12.2–13.2% SL; dorsal-to-adipose distance 23.0–24.8% SL; distally expanded neural spines in vertebrae between dorsal and adipose fins; body depth at anus 12.4–14.8%SL; post-adipose distance 18.7–20.3% SL; caudal-peduncle length 20.3–21.8% SL; caudal-peduncle depth 6.7–7.4%SL;40–41 vertebrae; reaching to at least ca. 170 mm TL in size; and uniformly dark-colored body generally devoid of pale or dark markings.